Pemberdayaan masyarakat melalui pemanfaatan kulit singkong menjadi stik aneka rasa di Kecamatan Kampar Utara Kabupaten Kampar - Eliza Eliza; Riswan Effendi; Shorea Khaswarina; Ermitety Ermitety; Novia Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The waste of cassava peel is thrown away by the community, cassava peel can be used as a variety of snacks including sticks. Sticks are an attractive, varied and easier to carry, can be an innovation in increasing people's income. The service activity aims to provide knowledge, skills and guidance to PKK mothers, UMKM people in processing products made from cassava peel into sticks in Kampung Panjang Village. This activity is expected to motivate the entrepreneurial spirit towards innovative and economical efforts to increase income. The method of this activity is counseling in the form of serving the benefits of cassava peel and training and guidance on how to process cassava skin into steak. The results of the community service are obtained: a) Participants knew the benefits and importance of training cassava peel processing as an alternative to household side activities, b) Activness the participants during the service shows a positive response seen from the enthusiasm, discussion, question and answer and good cooperation. c) The achievement level of the target program has been the participants who have applied the processing of cassava peel to sticks with various flavors.